Complementary therapies-based interventions on burnout outcomes: a meta-analysis - Esperança, M. B.; Ferreira, A.I.; Miraglia M. (EAWOP, 2022)
Mental illness at work has become more and more relevant not only as a topic of discussion but mostly of investigation. Inability to cope with daily problems, excessive fear or worries, withdrawal, feeling down, and tiredness are some of the signs of workplace mental health problems and can be revealed through absenteeism and presenteeism behaviours, changes in emotion and interpersonal conflicts, perceptions of work stressors and physical health, job satisfaction, organisational commitment, burnout and turnover intentions which in turn can jeopardise work performance (Auten & Fritz, 2018). From these outcomes, one of the least considered is health-related outcomes (e.g., emotional exhaustion, burnout) during which an employee may physically be at work but not fully engaged or focused on the daily tasks. The present meta-analysis aimed to quantify the effects of complementary therapies’ attendance on employees occupational burnout, with special interest in mindfulness, yoga therapy and acupuncture. This research is worthwhile because it represents an overview of the link between these complementary therapies and employees’ burnout levels, a link that was never made before. Although some companies underestimate employees’ mental and physical health impact on their productivity levels (Kigozi, Jowett, Lewis, Barton, & Coast, 2017), there is vast evidence linking employees’ health risks to higher financial costs (Howarth, Quesada, Silva, Judycki, & Mills, 2018). There is evidence suggesting that health intervention programs with complementary therapies report an effective improvement in general health status by reducing stress levels, anxiety, burnout and depression (Brämberg et al., 2017; Wolever et al., 2012) which in turn can reduce presenteeism and absenteeism behaviours in the workplace (Merrill, Aldana, Garrett, & Ross, 2011; Patel et al., 2010). Most studies regarding health interventions programs report an effective reduction in non-productive behaviours in the workplace (Merrill, Aldana, Garrett, & Ross, 2011; Patel et al., 2010), leading researchers to conclude that unhealthy lifestyle behaviours related with lower productivity are highly modifiable (e.g., poor management of health conditions, burnout, obesity, insomnia, lack of physical activity, etc.) (Howarth, et al., 2018). For instance, mindfulness-based programs have proven to reduce depression, stress, anxiety and burnout (Hülsheger et al., 2013; Jacobs et al., 2017; Jill et al., 2015; Patronis & Staffileno, 2021, Taylor & Harrison, 2013), and to significantly improve job satisfaction, employer-rated job performance (Hülsheger et al., 2013; Shonin et al., 2014) and sleep quality (Jacobs et al., 2017). Yoga has been proven to significantly reduce burnout (Alexander et al., 2015; Hilcove et al., 2020; Loewenthal et al., 2021; Kavurmaci, Tan &Turan, 2021), stress, anxiety and depression (Babbar, Renner, & Williams, 2019; Hilcove et al., 2020; Loewenthal et al., 2021; Mandal et al., 2021; Ofei-Dodoo et al., 2020) and proven to improve vitality, self-care, sleep quality (Alexander et al., 2015; Hilcove et al., 2020), personal accomplishment, perceived resilience (Ofei-Dodoo et al., 2020) and job satisfaction (Kavurmaci, Tan & Turan, 2021). Acupuncture has been indicated to reduce anxiety, burnout, and depression (Buchanan et al., 2018; Dias, Vellarde, & Olej, 2002; Dincera & DemetInangil, 2020; Reilly et al, 2014; Schaufeli et. al.,2002), and to improve sleep quality (Dias, Vellarde, & Olej, 2002) and work engagement (Buchanan et al., 2018; Schaufeli et. al.,2002). Based on this evidence, it is inevitable to believe that these three complementary therapies can be considered relevant in preventing burnout. There are meta-analysis combining results from workplace health promotion programs aiming to reduce burnout, and there are meta-analysis with programs based on complementary therapies, however, there is no meta-analysis that combines results from different complementary therapies and no recent meta-analysis on interventions to reduce burnout. Therefore, it would be important to have a meta-analysis combining these three therapies and burnout outcomes. We used the statement of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) flow diagram (Moher, Liberati, Tetzlaff, & Altman, 2009) to facilitate the collection and analysis of articles that contemplate complementary therapies-based interventions on health-related outcomes. Both in-person and web-based health interventions were included. Articles were screened and included if they met the following criteria: (a) the study was empirical, (b) the sample included a total of 10 or more participants, (c) the study included occupational population, (d) the study included mindfulness, yoga therapy or acupuncture intervention, (e) the study included at least one burnout related outcome. We examined 81 effect sizes in 55 studies. We are still collecting data and we will be able to bring these results to the event. We expect to obtain significant effects on the reduction of burnout, especially in studies involving mindfulness practices. Results are discussed in terms of their implications for employee’s burnout levels in the organisational context. Due to the content of this meta-analysis, it will be of interest to the academic audience and practitioners.